Kecemmasan menghadapi dunia kerja pada mahasiswa: Adakah peranan self-efficacy? - Seran, Maksimilian Ewaldus Seran; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2023)
Abstract Students have entered early adulthood where students have tasks such as working and building a career. Final-year students usually have started to think about choosing the world of work will be like, such as the place of work, opportunities to get a job, and competition in finding a job. That way students are required to have competence and expertise to compete in the world of work. There is a lot of competition in the world of work and a lack of jobs resulting in unemployment due to the difficulty of getting a job. One of the factors causing unemployment in Indonesia is the limited number of jobs that cannot accommodate all job seekers. This study aims to examine empirically whether there is a relationship between Self-Efficacy and Anxiety in Psychology Students at the University of 17 August 1945 Surabaya in Facing the World of Work. The method used in this study is quantitative, testing the data used in this study is a test of validity and reliability, while the analysis of research results using the normality test, linearity test, test the coefficient of determination (R2), and Product Moment Correlation test. The results of this study indicate that the normality test obtained a significance value of p = 0.054 > 0.05, which means that the data distribution is normal. Other tests were carried out using the Linearity test which produced an F value of 2.975 which could mean that there was a relationship between Self-Efficacy and Anxiety in facing the world of work in Psychology Students at the University of August 17 1945 Surabaya. Subsequent tests were carried out using the Spearman-Rho Correlation test method which produced a sig. of 0.000 which means that Self-Efficacy has a significant relationship with Anxiety. The correlation coefficient value is -0.332 which means that there is a negative relationship between Self-Efficacy and Anxiety in facing the world of work in Psychology Students at the University of August 17, 1945, Surabaya.